2017
DOI: 10.1186/s13018-017-0675-z
|View full text |Cite
|
Sign up to set email alerts
|

Peroneal artery perforator flap for the treatment of chronic lower extremity wounds

Abstract: BackgroundReconstruction of chronic lower extremity wounds remains challenging. These wounds are mainly associated with diabetes mellitus, infections, and osteomyelitis. Although several reconstructive techniques are available, the peroneal artery perforator flap has unique advantages.MethodsIn this study, we discuss our experiences with peroneal artery perforator flaps in 55 patients who had suffered from chronic lower limb wounds. The size of the defect, comorbidities, etiology, flap size, and complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Septocutaneous perforators anastomose with each other forming a microvascular suprafascial axis that stretches from the head of fibula to the tip of LM (11). Schaverein et al, after studying 30 specimens identified that the perforators from PA are not in clusters as reported by some studies, but they are distributed at different levels (13). Among the perforator flaps, the distal flap involves PP as a source vessel above the lateral malleolus (14).…”
Section: Discussionmentioning
confidence: 98%
“…Septocutaneous perforators anastomose with each other forming a microvascular suprafascial axis that stretches from the head of fibula to the tip of LM (11). Schaverein et al, after studying 30 specimens identified that the perforators from PA are not in clusters as reported by some studies, but they are distributed at different levels (13). Among the perforator flaps, the distal flap involves PP as a source vessel above the lateral malleolus (14).…”
Section: Discussionmentioning
confidence: 98%
“…13,31 When discussing skeletonized flaps, many authors described irrigation with some variety of vasodilator irrigation during the case to prevent spasm that is associated with increased handling of the vessel as the soft tissue attachments are stripped. 6,11,13,16,[31][32][33][34][35] Following dissection and pedicle skeletonization, the flap is then carefully transposed into the defect location, avoiding any tension on the pedicle. 31 During this systematic analysis several common themes emerged.…”
Section: Flap Dissectionmentioning
confidence: 99%
“…41 The protective effect of skeletonization in these instances may also be attributed to the reduction of redundant tissue that might otherwise compromise the blood supply to the flap, specifically venous drainage after flap rotation. 17,30,32,34,35,38,40 Venous congestion continues to be a major complication after pedicled flap transfer. 42,43 Veins are more susceptible to occlusion following rotation due to their low pressure and thin walls.…”
Section: Flap Typementioning
confidence: 99%
See 1 more Smart Citation
“…Multiterritory perforator flap have been widely used in clinics for a long time to repair skin defects such as congenital disorders, trauma, tumor ablation, and diabetic foot ulcer ( Cheng et al., 2017 ). Previous studies have revealed that necrosis usually occurs away from the boundary between potential and dynamic territory ( Taylor et al., 1992 ; Fichter et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%